Family Policy Aimed at Demographic Incentives in EU Law - Korom, Ágoston (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter examines the discretion conferred on the Member States of the European Union (EU) in relation to the application of family policy that aims to improve the demographic situation. Incentives for childbearing in pension schemes, as well as the status of the family and the related subsidies, fall within the competence of the Member States. The European Commission generally formulates recommendations in that regard, which lack binding force. Nonetheless, in these fields, the Court of Justice of the European Union (CJEU) gives effect to primary and secondary EU law ensuring equal treatment of men and women. State subsidies with objectives related to demography do not ‘prevail’ in the case law of the CJEU. Examining the ratio decidendi of the existing case law, it is clear that this is not limited to the acknowledgement of childbearing in pension schemes but covers all state subsidies with similar objectives. In my opinion, this case law is a major obstacle to achieving the related national goals; thus, it is necessary to harmonise the EU law in force and the objectives related to demography. Keywords: state subsidies; demography; case law; CJEU; marital status; subsidies; competence; Member States; EU law; national legislature on family status; demographic objectives; solutions